Application of nanoscratching in electronic devices - Ramiączek-Krasowska, Maria; Szyszka, Adam; Prażmowska, Joanna; Paszkiewicz, Regina; Tłaczała, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The lithography is a basic operation in the fabrication process of semiconductor devices. The scaling ability is the reason why the atomic force microscopy (AFM) nanolithograpy is currently studied in many laboratories. In the paper, the results of the mechanical AFM lithography, named nanoscribing or nanoscratching, are presented. In this method, the pattern is created by mechanical interaction between the AFM tip and a sample. This interaction requires the application of large forces in micronewtons scale.
Optica Applicata, Vol. 39, 2009, nr 4, s. 711-716
Keywords: optyka; nanolithography; nanoscratching; AFM lithography